Developing a Multi-factor Authentication-based Cardless Electronic Payment System. Issue 1 (March 2021) - Ayo, C.K; Mac-Eze, C.M; Adebiyi, A.A.; Oni, A.; Okesola, J.O.; Odun-Ayo, I.
Abstract: The Nigerian economy is still largely cash based arising from inadequate infrastructure, trust and instability in the banking sector. However, there are improvements in the adoption of the electronic platform through the concerted efforts of government by introducing some policies that encourage its use. The recent policy is the cashless policy, which is aimed at reducing the use of cash to the barest minimum. This paper is aimed at developing an electronic payment system that integrates all the bank accounts of a particular holder together and access granted to them with or without a payment card through a multi-factor authentication procedures such as pin, fingerprint, irish or 3D facial recognition. On a full implementation, this system incorporates additional security protocol on the device to avoid nonrepudiation and ensure that the user is actually who he claims to be. The system will enhance ease of use as well as simplify the use of the e-Payment channels.